Values or appraisements. Anthropology’s contributions in bioethics research - Álvarez Licona, Nelson Eduardo (Acta Bioethica, 2007)
This paper analyzes anthropology's contribution to bioethics, related to its methodology and theoretical frameworks of reference. It affirms that most confusions arise from the mechanic application of the so called "universal values" which would be solved if, when interpreting moral behavior, we understood that we are not considering values but appraisements..